Myositis ossificans traumatica of the left masseter muscle presenting as soft tissue mass: a case report - Ahmad, Kaleem; Ansari, Sajid; Dhungel, Kanchan; Gupta, Mukesh Kumar; Rauniyar, RK; Amanullah, Md Farid (Bangladesh Journal of Medical Science, 2013)
Myositis ossificans is a rare disease in which manifests as heterotopic bone formation within a muscle and is rarely found in the head or neck regions, including the masticator muscle. It should be considered as a differential diagnosis in patients of trauma with severe limitation of jaw opening. Panoramic radiographs and axial and coronal computed tomography (CT) scans can effectively delineate the calcified mass. Other imaging studies that may be helpful include magnetic resonance imaging (MRI), bone scans, and ultrasound. DOI: http://dx.doi.org/10.3329/bjms.v13i1.17441 Bangladesh Journal of Medical Science Vol. 13 No. 01 January2014: 73-75